Gambaran kepuasan pasien rawat jalan terhadap pelayanan kesehatan di UPT Kesmas Payangan, Gianyar, Bali - Ni Kadek Novi Antari (Intisari Sains Medis, 2019)
Background: Health service is any efforts held by personal or together in an organization to maintain and increasing health as well as patient’s satisfaction. This study aims to know the outpatient patients’ satisfaction representation toward health service in UPT Kesmas Payangan.Methods: A cross-sectional descriptive study was conducted among 85 outpatient at UPT Kesmas Payangan. Sample technique used in this study was convenience sampling method. Samples are outpatient patients who were visiting UPT Kesmas Payangan and assesses using valid and reliable questionnaire regarding patient’s satisfaction based on 5 dimensions (tangible, reliability, responsiveness, assurance, empathy). Data were analyzed using SPSS version 20 for Windows.Results: Most of outpatient are satisfied at UPT Kesmas Payangan (88.2%). Based on satisfaction dimension, our study found that more patients are satisfied in reliability (82.3%), responsiveness (94.1%), assurance (92,9%), tangibles (84.7%), and empathy (88,2%). In addition, female patients are more satisfied (91,3%) than males (84,6%), following by lower level of education is more satisfied (95,2%) as well as in jobless group (100%) compared with others. According to the method of payment, group that using out of pocket method is more satisfied (90%) than using BPJS health insurance (88%).Conclusion: Most of outpatients at UPT Kesmas Payangan are satisfied with health services provided particularly in responsiveness dimension. Out of pocket as method of payment is also tend to given higher satisfaction than BPJS health insurance.